S.IBRAGIMOV LIRIKASÍNÍŃ KOMPOZICIYASÍ - Orınbaeva, Aziza (SCIENCE and SOCIETY, 2026)
The article analyzes the lyrical works of the talented poet So’g’inboy Ibragimov. The poet’s artistic explorations in applying compositional techniques in his lyrics are illustrated through the context of his works. In lyrical poems, the significance of compositional techniques in imbuing a work with unique artistry and shaping its content and form has been analyzed with examples.